The Linear Stability of a Power-Law Liquid Film Flowing Down an Inclined Deformable Plane - Karim Ladjelate; Nadia Mehidi Bouam; Amar Djema; Abdelkader Belhenniche; Roman Chertovskih (Mathematics)
A linear stability analysis is performed for a power-law liquid film flowing down an inclined rigid plane over a deformable solid layer. The deformable solid is modeled using a neo-Hookean constitutive equation, characterized by a constant shear modulus and a nonzero first normal stress difference in the base state at the fluid–solid interface. To solve the linearized eigenvalue problem, the Riccati transformation method, which offers advantages over traditional techniques by avoiding the parasitic growth seen in the shooting method and eliminating the need for large-scale matrix eigenvalue computations, was used. This method enhances both analytical clarity and computational efficiency. Results show that increasing solid deformability destabilizes the flow at low Reynolds numbers by promoting short-wave modes, while its effect becomes negligible at high Reynolds numbers where inertia dominates. The fluid’s rheology also plays a key role: at low Reynolds numbers, shear-thinning fluids (<semantics>n<1</semantics>) are more prone to instability, whereas at high Reynolds numbers, shear-thickening fluids (<semantics>n>1</semantics>) exhibit a broader unstable regime.